2020
DOI: 10.1038/s41467-020-15461-z
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing of familial high-grade serous ovarian carcinoma reveals heterogeneity for rare candidate susceptibility genes

Abstract: High-grade serous ovarian carcinoma (HGSOC) has a significant hereditary component, approximately half of which cannot be explained by known genes. To discover genes, we analyse germline exome sequencing data from 516 BRCA1/2-negative women with HGSOC, focusing on genes enriched with rare, protein-coding loss-of-function (LoF) variants. Overall, there is a significant enrichment of rare protein-coding LoF variants in the cases (p < 0.0001, chi-squared test). Only thirty-four (6.6%) have a pathogenic variant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 82 publications
3
32
0
1
Order By: Relevance
“…As has been reported with all of these examples of CPGs in non-FC populations, we expected an array of potentially pathogenic variants in our candidate gene. Indeed, we observed eight potentially pathogenic FANCI variants in AUS HGSC cases, which included c.1813C>T. A recent genome-wide discovery study of AUS HGSC cases did not report FANCI among the list of potentially new CPGs for OC 74 . However, the missense FANCI variants found in our analysis of AUS samples, which were investigated in both studies, would have been excluded due to a focus on LoF variants 74 .…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…As has been reported with all of these examples of CPGs in non-FC populations, we expected an array of potentially pathogenic variants in our candidate gene. Indeed, we observed eight potentially pathogenic FANCI variants in AUS HGSC cases, which included c.1813C>T. A recent genome-wide discovery study of AUS HGSC cases did not report FANCI among the list of potentially new CPGs for OC 74 . However, the missense FANCI variants found in our analysis of AUS samples, which were investigated in both studies, would have been excluded due to a focus on LoF variants 74 .…”
Section: Discussionmentioning
confidence: 60%
“…Indeed, we observed eight potentially pathogenic FANCI variants in AUS HGSC cases, which included c.1813C>T. A recent genome-wide discovery study of AUS HGSC cases did not report FANCI among the list of potentially new CPGs for OC 74 . However, the missense FANCI variants found in our analysis of AUS samples, which were investigated in both studies, would have been excluded due to a focus on LoF variants 74 . Our investigation of HGSC cases from the AUS population thus also suggest that FANCI variants may also play a role in OC in non-FC populations.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the recent past, the combination of microarray technology and bioinformatics has facilitated the understanding of molecular mechanisms and reliable diagnostic and therapeutic targets for diseases. Through these techniques, many new genes involved in complex human diseases such as cancer and autoimmune complications have also been discovered [ 6 , 7 ]. Several studies have identified disease-related genes and functional pathways by analyzing the expression profile between SLE and healthy controls [ 8 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Loss-of-function variants in the MMR genes MLH1, MSH2, MSH6 and PMS2 have been reported as risk factors for clear cell and endometrioid ovarian carcinomas [15,21]. Loss-of-function variants in the HDR genes BRCA1, BRCA2, PALB2, BRIP1, RAD51C and RAD51D have been described, among others, to strongly increase the risk for serous ovarian cancer [19,[21][22][23][24][25]. In addition, evidence has been accumulated that deleterious variants in HDR genes are also predictors of therapeutic outcome [16,18].…”
Section: Introductionmentioning
confidence: 99%